استفادة الأحكام الشرعية من وجه دلالة القرآن الكريم في ضوء الموافقات الشاطبية - Muslihun Muslihun (Universitas Yudharta Pasuruan, 2019)
This article explains the reading of meaning of the Qur’an with al-Syatibi theory in the book entitled “al-muwaqat”. This article employs hermeneutical approach to understand the narrative studies of the text by Emilio Betti. He gives some hermeneutical principles, namely: 1. Reproductive interpretation which exists in performing the text. 2. Explicative interpretation supposed that we intend to attain a reproductive interpretation, which is the important one, since it makes the text present and live. Before obtaining the purpose (maqasid syariah) of islamic law, Syathibi wrote semantics to be a way to view maqasid syariah because both the text and the purpose cannot be separated from interpretation theory. Therefore, this thesis aims to explore how al-Syatibi reveals a whole meaning of the Qur’an.